Efektivitas Posisi Bersalin terhadap Lama Kala II Persalinan: Effect of Maternity Position on the Length of Second Stage of Labor - Hardjanti, Triana Sri; Suparmi; Sunarto (Indonesian Journal of Midwifery (IJM), 2024)
The position of the mother during the birthing process can be freely changed or modified according to the wishes of the birthing mother. The birthing mother therefore receives fewer opportunities for labor and delivery in the preferred position, assuming the supine one as the standard due to easier monitoring of fetal well-being, administration of intravenous therapy, locus-regional anesthesia, and performance of medical procedures, perineal support, and birth assistance. Effects of different maternal positions during labor on maternal and neonatal outcomes. The purpose of this study was to analyze the effect of maternity positions on the length of the second stage of labor in the city of Semarang. This research was conducted at Midwife Independent Practice (PMB): Eka Setyowati, Sudiyah Proborini, Amelia & Sukateni. The type of research is Quasy-Experimental with a Post-Test Only with Control Group design. The population in this study were all birthing mothers with term pregnancies. The sampling technique is by using the accidental sampling technique. The research sample was 40 respondents. Data distribution analysis used Shapiro-Wilk, simple linear regression to determine the effect of birth position on the length of the second stage of labor, and multiple linear regression to determine the effect of maternity position on the length of the second stage of labor which was controlled by the age of the birthing mother. The results of the research show that for every 1 year increase in a pregnant woman's age, the length of the second stage will accelerate by 0.8 hours faster. Mothers who gave birth in the lateral position experienced the second stage of labor 1.8 hours faster than mothers who gave birth in the lithotomy position. Acceleration of the second stage of labor in pregnant women in the lateral position was not significant (B= -1.8, 95%CI: -13.4-9.7, p = 0.751). The effectiveness of the lateral position in accelerating the length of the second stage of labor is 0.03%. It is hoped that the results of this study will give birthing mothers the awareness to always pay attention to the condition of their bodies, so that all prospective pregnant women can plan for pregnancy at a productive age (20–35 years), because within this age range the reproductive organs work optimally. The mother should choose a position as comfortable as possible, namely the position that is more or the most effective in accelerating the progress of the second stage of labor.   Abstrak Posisi ibu selama proses persalinan bisa bebas diubah atau dimodifikasi sesuai dengan keinginan ibu melahirkan. Ibu melahirkan menerima lebih sedikit kesempatan untuk persalinan dan melahirkan dalam posisi yang disukai, dengan asumsi yang telentang sebagai standar karena lebih mudah pemantauan kesejahteraan janin, pemberian terapi intravena, anestesi lokus-regional, dan kinerja prosedur medis, dukungan perineum, dan bantuan kelahiran. Efek dari posisi ibu yang berbeda selama persalinan pada hasil ibu dan neonatal. Tujuan dari penelitian ini yaitu untuk menganalisis efektifitas posisi bersalin terhadap lama kala II persalinan di kota Semarang. Penelitian ini dilakukan di Praktik Mandiri Bidan (PMB): Eka Setyowati, Sudiyah Proborini, Amelia & Sukateni. Jenis penelitian ini Quasy-Eksperimental dengan rancangan Post-Test Only with Control Group. Populasi penelitian Populasi pada penelitian ini yaitu semua ibu bersalin dengan kehamilan aterm. Teknik pengambilan sampel yaitu dengan menggunakan tehnik accidental sampling. Sampel penelitian 40 responden. Analisis distribusi data menggunakan Saphiro-Wilk, Regresi linier sederhana untuk mengetahui efek posisi bersalin terhadap lama kala II persalinan, dan Regresi linier ganda untuk mengetahui efek posisi bersalin terhadap lama kala II persalinan yang terkontrol oleh usia ibu bersalin. Hasil penelitian menunjukkan bahwa setiap kenaikan umur ibu hamil 1 tahun akan terjadi percepatan lama kala 2 sebesar 0.8 jam lebih cepat. Ibu bersalin dengan posisi lateral mengalami kala II persalinan 1.8 jam lebih cepat dibandingkan dengan ibu bersalin dengan posisi Lithotomi. Percepatan kala II persalinan pada ibu hamil dengan posisi lateral tidak signifikan (B= -1.8, 95%CI: -13,4-9.7, p = 0.751). Efektifitas posisi lateral dalam mempercepat lama kala II persalinan sebesar 0.03%.